INTERVENSI PEKERJA SOSIAL DALAM REUNIFIKASI EKS GANGGUAN JIWA DI BALAI REHABILITASI SOSIAL BINA KARYA DAN LARAS (BRSBKL) YOGYAKARTA - Fahri Alia; Tri Shandra Abridinata Wibowo; Hendrik Basguni Sukendar; Ekmil Lana Dina (UIN Sunan Kalijaga Yogyakarta, 2018)
Abstract Factors of poverty, low education, divorce cause is often referenced as the brain's disease. There is a significant relationship between problems experienced by a person with his behavior. Because, often people who are experiencing problems are always included with changes in behavior that is not unusual. This behavioral change is then done through a behavioral approach to restore the behavior as it once was. In this case as conducted by the Social Rehabilitation Bina Karya and Laras (BRSBKL) to ex mental disorders. Clients who initially are someone who lives in a normal society, then when experiencing problems change drastically all his behavior becomes angry, quiet, aloof, not confident or afraid. But after receiving behavioral assistance then the clients are slowly experiencing a significant development into a person who would open, independent living, courage, mutual cooperation or already able to activity daily living.But in the process, not all clients who experience exs psychiatric disorders can be predicted when they will be healthy again. This can be seen from the level of problems and the desire of the client to return to health. Therefore, the handling of psychological exs through a behavioral approach can not be ascertained when it will end.Keywords: Behavioral theory, Mental Disorders, Rehabilitation.